Educação escolar Quilombola na Lagoa dos Crioulos no Cariri cearense: uma perspectiva curricular de afroaquilombamento - Santos, Ana Paula dos (2023)
This present proposal of thesis aims to understand how quilombola school education dialogues with the cultural repertoires of the community, based on a proper pedagogy. The research locus was constituted in two quilombola schools in the Region of Cariri in the community of Quilombola Lagoa dos Crioulos: Luiz Rodrigues da Fonseca Children's Education Center and the João Rodrigues da Fonseca Fundamental Education School. In this way, the general objective of the thesis is to analyze the specificities of the knowledge transmission practices of the quilombola community with a view to the construction of a pedagogical proposal of Afroaquilobamento for the quilombo schools. This proposal unfolds in the following specific objectives: to identify a pedagogy that characterizes quilombola education based on two sociocultural and historical repertoires of the researched communities, particularly experiences of ancestral values; raise the demands of the communities not referring to quilombola school education; to investigate how community practices can be afroaquilombar a differentiated pedagogy for the schools two quilombos. The research is qualified as qualitative with ethnographic characteristics with a focus on educational aspects, with teachers and quilombola communities as interlocutors. The research used, for the production of data, collective interviews organized and adapted from a focus group, participant observation, annotations in field records. For the analysis of the data, the concept and methodological steps established by Afrodescendants were used. We conclude, from two findings of the research that the quilombola communities are teaching ethnic groups that have the possibility of contributing as Afro to the development of the curriculum from pedagogies referenced in the quilombola cultural repertoire.